The Influence Of Soft Skills, Hard Skills, Self-Efficacy, And Motivation Of Accounting Students On Student Work Readiness In The Era Of The Industrial Revolution 4.0 - Royani, Syara Syalbiah; Ningsih, Endang Kusdiah; Dini, Maya (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2024)
The purpose of this research is to determine and analyze the influence of soft skills, hard skills, self-efficacy, and motivation on the job readiness of students, both simultaneously and partially, in facing the workforce. The population of this study consists of 1,613 students, calculated using the Slovin formula with a 5% margin of error, resulting in 323 respondents from the accounting study program from the 2021 to 2023 cohorts. The method used is multiple linear regression analysis with the help of SPSS 22 testing tools. The data instruments used for testing are validity and reliability tests, with data analysis employing classical assumption tests. The research findings reveal that simultaneously, the variables of Soft Skills, Hard Skills, Self-Efficacy, and Motivation significantly affect the job readiness of accounting students in the Era of the Industrial Revolution 4.0.